Pengaruh Pemberian Pupuk Kascing Dan Cangkang Telur Ayam Terhadap Pertumbuhan Dan Produksi Terong Bulat Pondoh (Solanum Melongena L.) - Paulus Diego Sinaga; Neng Susi; Seprita Lidar (JURAGAN - Jurnal Agroteknologi, 2023)
One of the reasons for the low eggplant production in Riau is that the soil type in Riau is generally Red Yellow Podzolik (PMK). Utilization of PMK soil as a medium for plant growth is faced with various problems, especially the physical, chemical and biological properties of the soil which are less supportive for growth. To be able to improve PMK soil, it is necessary to provide a lot of organic matter, such as vermicompost fertilizer. Vermicompost organic fertilizer is an organic fertilizer plus, because it contains macro and micro nutrients and growth hormones that are readily absorbed by plants. In addition, giving egg shells is a household waste that can still be used to fertilize plants. Eggshell contains 94% calcium carbonate, 1% calcium phosphate, 1% magnesium carbonate and 4% organic compounds (Rahmawati and Nisa, 2015). The high calcium carbonate contained in eggshells can be used as an alternative source of calcium. The purpose of this study was to determine the effect and the best combination of casting and chicken eggshell fertilizer on the growth and production of pondoh round eggplant (Solanum melongena L.). This research was carried out experimentally using a factorial Completely Randomized Design (CRD), which consisted of two factors, namely K (Kascing Fertilizer) consisting of 3 levels, and factor C (Chicken egg shells), consisting of 3 levels, each consisting of 3 repetitions, The number of experimental units is 27 plots, each plot consists of 4 plants and 2 plants as samples, so that the total plant is 27 x 4 = 108 plants. The result of this research is that the interaction of vermicompost fertilizer and chicken egg shells has a significant effect on plant height, stem diameter, number of fruits, fruit weight per plant, fruit diameter of eggplant plants, by giving 100 g of castor fertilizer/plant and 30 chicken egg shells. g/plant is the best dose in this study.